An evaluation of the relationship between Enterobius vermicularis infestation and acute appendicitis in a paediatric population – A retrospective cohort study. (June 2015) - Fleming, C.A.; Kearney, D.E.; Moriarty, P.; Redmond, H.P.; Andrews, E.J.
Abstract: Background: Enterobius vermicularis is an often unexpected finding in appendectomy specimen, most commonly seen in paediatric cases. Predicting the presence of E. vermicularis in the setting of appendectomy is important to avoid unnecessary appendectomy and associated morbidity. We sought to identify the incidence of E. vermicularis in a paediatric population undergoing appendectomy for clinically suspected acute appendicitis and identify predictive factors for E. vermicularis . Methods: This study was performed in an 800-bed University Teaching Hospital, in the Republic of Ireland. We identified all paediatric appendectomies performed at our institute from January to December 2012 using prospectively maintained operating theatre logbooks. In-hospital Histopathology database, medical notes and operative findings were reviewed for each patient and relevant data recorded. Statistical analysis was performed using IBM SPSS, version 21. Results: In total 182 paediatric appendectomies were performed during the year 2012 for clinically suspected acute appendicitis. Demographics included: Mean age 11.14 years (3–16), gender 1M: 1F. 58.8% of procedures were completed laparoscopically, 39% open and 2.2% were converted. The negative appendectomy rate was 22.5%. The annual incidence of E. vermicularis in acute appendicitis specimen from a paediatric cohort at our institute was 7% (1 in 14). In specimen containing E. vermicularis, 69% had no evidence of appendicitis and of those that had, no gangrene or perforation was seen. The presence of E. vermicularis in paediatric patients with RIF pain may be predicted by Eosinophilia (p = 0.016), normal WCC (p = 0.034) and normal Neutrophil count (p = 0.014). Conclusions: E. vermicularis is responsible for 7% of acute appendicitis. It is responsible for a significantly higher negative appendectomy rate which if predicted may avoid unnecessary appendectomy and associated morbidity. Highlights: The presence of Enterobius vermicularis may mimic acute appendicitis. Predicting patients with E. vermicularis may avoid unnecessary surgery. E. vermicularis infestation may be seen in as many as 7% of paediatric patients undergoing appendectomy. E. vermicularis is associated with a significantly high negative appendectomy rate. The presences of E. vermicularis may be predicted by eosinophilia with a normal white cell and neutrophil count.